Alpha-melanocyte-stimulating hormone is present in the inferior petrosal sinuses in patients with Cushing's disease - Colao, A; Merola, B; Cataldi, M; La Tessa, G; Boudouresque, F; Oliver, C; Di Renzo, G; Annunziato, L; Lombardi, G (Neuroendocrinology, 1993)
Plasma ACTH, beta-endorphin and alpha-melanocyte-stimulating hormone levels were evaluated in the inferior petrosal sinuses and in the periphery of 22 patients affected by Cushing's disease, 11 patients with other pituitary diseases subjected to simultaneous and bilateral inferior petrosal sinus sampling and in the peripheral blood of 15 normal subjects. In patients with Cushing's disease ACTH, beta-endorphin and alpha-melanocyte-stimulating hormone levels in the inferior petrosal sinus ipsilateral to the adenoma were significantly higher than in the periphery and in the contralateral inferior petrosal sinus (p < 0.01, p < 0.01 and p < 0.05, respectively). In patients with other pituitary diseases only ACTH and beta-endorphin, but not alpha-melanocyte-stimulating hormone levels in both inferior petrosal sinuses were significantly higher than in the periphery (p < 0.01). Furthermore, no difference was found in the peripheral blood among patients with Cushing's disease, patients with other pituitary diseases and normal subjects for ACTH and beta-endorphin level. By contrast, in patients with Cushing's disease peripheral alpha-melanocyte-stimulating hormone levels were significantly higher than in patients with other pituitary diseases and in normal subjects (p < 0.05). In conclusion, the results of the present study suggest that only in patients with Cushing's disease, but not in patients with other pituitary diseases, alpha-melanocyte-stimulating hormone is released by adenomatous pituitary corticotrophs together with ACTH and beta-endorphin.